P5CDH affects the pathways contributing to Pro synthesis after ProDH activation by biotic and abiotic stress conditions - Rizzi, Yanina S.; Monteoliva, Mariela I.; Fabro, Georgina; Grosso, Carola L.; Laróvere, Laura E.; Alvarez, Maria E. (Frontiers in Plant Science, 2015)
Plants facing adverse conditions usually alter proline (Pro) metabolism, generating changes that help restore the cellular homeostasis. These organisms synthesize Pro from glutamate (Glu) or ornithine (Orn) by two-step reactions that share Δ1 pyrroline-5-carboxylate (P5C) as intermediate. In the catabolic process, Pro is converted back to Glu using a different pathway that involves Pro dehydrogenase (ProDH), P5C dehydrogenase (P5CDH), and P5C as intermediate. Little is known about the coordination of the catabolic and biosynthetic routes under stress. To address this issue, we analyzed how P5CDH affects the activation of Pro synthesis, in Arabidopsis tissues that increase ProDH activity by transient exposure to exogenous Pro, or infection with Pseudomonas syringae pv. tomato. Wild-type (Col-0) and p5cdh mutant plants subjected to these treatments were used to monitor the Pro, Glu, and Orn levels, as well as the expression of genes from Pro metabolism. Col-0 and p5cdh tissues consecutively activated ProDH and Pro biosynthetic genes under both conditions. However, they manifested a different coordination between these routes. When external Pro supply was interrupted, wild-type leaves degraded Pro to basal levels at which point Pro synthesis, mainly via Glu, became activated. Under the same condition, p5cdh leaves sustained ProDH induction without reducing the Pro content but rather increasing it, apparently by stimulating the Orn pathway. In response to pathogen infection, both genotypes showed similar trends. While Col-0 plants seemed to induce both Pro biosynthetic routes, p5cdh mutant plants may primarily activate the Orn route. Our study contributes to the functional characterization of P5CDH in biotic and abiotic stress conditions, by revealing its capacity to modulate the fate of P5C, and prevalence of Orn or Glu as Pro precursors in tissues that initially consumed Pro.